2023
DOI: 10.3389/fendo.2023.1221259
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12, folate, and homocysteine in metabolic syndrome: a systematic review and meta-analysis

Juan R. Ulloque-Badaracco,
Enrique A. Hernandez-Bustamante,
Esteban A. Alarcon-Braga
et al.

Abstract: Background & aimsMetabolic syndrome (MetS) is associated with life-threatening conditions. Several studies have reported an association of vitamin B12, folic acid, or homocysteine (Hcy) levels with MetS. This systematic review and meta-analysis assessed the association of vitamin B12, folic acid, and Hcy levels with MetS.MethodsPubMed, Scopus, Embase, Ovid/Medline, and Web of Science were searched up to February 13, 2023. Cross-sectional, case-control, or cohort studies were included. A random-effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Additionally, the ameliorating effect of vitamin B12 on metabolic disorders may also contribute to lower odds of ischemic stroke. A meta-analysis revealed an inverse association between higher vitamin B12 levels and metabolic syndrome (OR = 0.87; 95% CI: 0.81–0.93; p < 0.01) [ 35 ]. Animal studies have shown that low vitamin B12 levels lead to lipid accumulation in adipocytes, inhibit β-oxidation of fatty acids and lipolysis in hepatic tissues, thus triggering dyslipidemia in mice [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the ameliorating effect of vitamin B12 on metabolic disorders may also contribute to lower odds of ischemic stroke. A meta-analysis revealed an inverse association between higher vitamin B12 levels and metabolic syndrome (OR = 0.87; 95% CI: 0.81–0.93; p < 0.01) [ 35 ]. Animal studies have shown that low vitamin B12 levels lead to lipid accumulation in adipocytes, inhibit β-oxidation of fatty acids and lipolysis in hepatic tissues, thus triggering dyslipidemia in mice [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ulloque-Badaracco et al . ( Ulloque-Badaracco et al, 2023 ) identified a significant correlation between elevated Hcy levels and MetS. You et al .…”
Section: Potential Mechanisms Linking Nnmt To Metsmentioning
confidence: 98%
“…This includes examining the frequency of food consumption across different groups, assessing the extent of deficiencies in individuals with ASD, and exploring their dietary preferences. Additionally, aside from inflammatory factors, elevated blood homocysteine levels have been linked to various neurological and mental disorders, including autism [ 17 , 18 ].. Homocysteine is an amino acid involved in methylation reactions and the metabolism of folate and vitamin B12 [ 19 ]. It can have neurotoxic effects, impacting neuronal function, neurotransmitter synthesis, and oxidative stress levels [ 20 ].…”
Section: Introductionmentioning
confidence: 99%